RETRACTED: Creation of digital maps of land disturbed by mining operations - Umarov Talent; Abdiev Aziz; Moldobekov Kubanychbek; Mambetova Rakhat; Abdiev Arstanbek; Isaev Bolot (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001